The relationship between shooting performance and respiratory muscle strength in archers aged 9-12 - Bostanci, O.; Kabadayi, M.; Mayda, M. H.; Yilmaz, A. K.; Yilmaz, C. (Baltic Journal of Health and Physical Activity, 2021)
Introduction: The aim of this study is to investigate the relationship between shooting performance and pulmonary functions and respiratory muscle strength in archers. Material and methods: The research was conducted with 31 boy and 11 girl archers aged 9-12. The forced vital capacity (FVC), forced expiration volume in one second (FEV1), FEV1/FVC, peak expiratory flow (PEF), maximum voluntary ventilation (MVV), maximum inspiratory pressure (MIP), and maximum expiratory pressure (MEP) of the archers were measured. To determine the shooting performance, a total of 30 shots (15+15) were taken from an 18-meter distance in closed shooting range. Results: A significant difference was found between the 15 shots done in each half and the total shot point and the averages of FVC (r=0.375, 0.353, 0.378 respectively) and FEV1 (r=0.368, 0.339, 0.367 respectively). However, a significant difference was not found among these shot points and other respiratory parameters (p>0.05). A relationship was detected between the second 15-shot points of boy archers and MEP (r=0.370). Conclusions: A strong correlation was not found between the respiratory parameters and shooting performances of the archers in this study. However, it is thought that this level of relationship will rise as training level and age increases.